EXPERIMENTAL STUDY OF STRUCTURAL-MECHANICAL PROPERTIES OF HEAVY OIL - BAYAMIROVA, Ryskol; TOGASHEVA, Aliya; ZHOLBASSAROVA, Akshyryn; ISLAMBERDIYEV, Zharas; BISSENGALIEV, Max; SUIEROV, Daden (Studia Universitatis Babeș-Bolyai Chemia, 2020)
Structural-mechanical properties of heavy oil from Kazakhstan deposits under the heat treatment were studied in this work. The most important and the least studied issues in the technology for the preparation and collection of oil products is the evaluation of the structural and mechanical properties of heavy oils and emulsions and ways to regulate formation them. A feature of the wells operation of fields with high viscosity oils is a sharp increase in water cut at the initial stage of development, which is associated with an excessively large difference in the rheological characteristics of reservoir oil and water. The formation of stable emulsions does not allow for the effective separation of oil from water and leads to a deterioration in product quality. In this regard, in modern conditions of intensification of hydrocarbon production, consideration of the options for the formation and destruction of complex emulsions is a prerequisite for the effective operation of oilfield treatment facilities. Therefore, the research relevance is of reducing the irretrievable losses of hydrocarbons in production systems and study the physical-chemical, structural-mechanical properties of heavy oils emulsions and to develop methods for their regulation, as well as improving oil treatment devices.